Competitiveness Analysis of Regencies and Cities in West Java Province - Bayu Kharisma; Sutyastie Soemitro Remi; Yudha Hadian Nur (Economics Development Analysis Journal, 2019)
Regional economic competitiveness aims to provide sustainable economic growth, namely developing leading sectors in accordance with the potential and needs of the region in order to improve the welfare of the community. This research aims to determine regional competitiveness in 4 (four) regencies and cities in West Java Province including The City and Regency of Bogor, Karawang Regency, Purwakarta Regency, Cirebon Regency, Indramayu Regency and Garut Regency. The research method used are the Analytical Hierarchy Process (AHP) and Kendall's Coefficient of Concordance as its methodology with competitiveness indicators of the regional economy, infrastructure, institution, social and political aspects, natural resources, and human resources. The results showed that the quality of human resources is the key to successful regional competitiveness. Thus, the implementation of regional competitiveness to achieve sustainable economic development in the 4 (four) regencies/cities in West Java Province should be directed towards the development of human resources through quality education, dependency ratio reduction, worker productivity increase, unemployment rate decrease, health service improvement, and purchasing power enhancement to strengthen the foundation of sustainable development, increase regional competitiveness, and direct orientation towards economic globalization.